SEEKING A PLACE IN A RELIGIOUS COMMUNITY: AN EXPLORATION OF PERSONAL EXISTENCE AMONG STUDENTS WITHOUT FAITH-COMMITMENT IN INDONESIA. - Prasasti Peranginangin; Denni Boy Saragih; Yanny Yeski Mokorowu (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2022)
Living without faith commitment is an existential struggle in Indonesia, where religion is essential for communal life. Despite the civic requirement to register one’s religious belief, some students, in reality, live without faith commitment. Their formal religious status is not a reflection of their convictions. They never attend religious worship, and they also have no idea about the core beliefs. Using qualitative phenomenological research, this article reports students’ existential struggle in a religiously-shaped society as an intense experience and struggle to find a place in the community. In the final part of the research, the paper also reflects the biblical perspective and provides recommendations for the church in the contemporary context.